Unexpected In Vivo Activity of Ceftazidime Alone and in Combination with Avibactam against New Delhi Metallo-β-Lactamase-Producing Enterobacteriaceae in a Murine Thigh Infection Model - MacVane, Shawn H. (Antimicrob Agents Chemother, 2014)
The emergence of the New Delhi metallo-β-lactamase (NDM) among Enterobacteriaceae has become a global concern because of its high levels of in vitro resistance to nearly all available antibiotics. However, recent in vivo studies demonstrated the efficacies of carbapenems against NDM-1-producing isolates despite high MICs. Herein, we report in vivo findings with ceftazidime and ceftazidime-avibactam against an isogenic pair (wild type and NDM-1) and four clinical NDM-producing isolates that demonstrate discordance between MICs measured in vitro and the in vivo activity of ceftazidime-avibactam against this resistant genotype.